Անհատական լեզվաշխարհի շերտային դրսևորումները (ըստ Էդ. Աթայանի՝ մարդկության կյանքի մակրոփուլերի տեսության) - Հովհաննիսյան, Ս. Գ.
В развитии языкового мира можно выделить 3 этапа, первый из которых-просто этап накопления языковых знаний, параллельно с которым происходит процесс познания действительности человека, второй-процесс укрепления этого знания, а третий-этап анализа и отчуждения накопленного знания, благодаря которому происходит совершенствование психического и языкового миров человека вплоть до его превращения в культурную ценность. There are 3 stages in the development of the language world, the first of which is simply the stage of accumulation of elementary knowledge through the language signs, in parallel with which the process of cognition of human reality takes place, the second is the process of strengthening this knowledge, and the third is the stage of analysis and alienation of accumulated knowledge, thanks to which the psychical and language worlds of a person are improved up to its transformation into a cultural value.
Keywords: Լեզվաբանություն